Interpretation of Art. 54 of the Convention Implementing the Schengen Agreement - Losy, Oskar (Przegląd Prawniczy Uniwersytetu im. Adam Mickiewicza, 2020)
The paper discusses the problem of the ne bis in idem principle stipulated in the Convention Implementing the Schengen Agreement (CISA) and the Charter of Fundamental Rights of the European Union. Article 54 of the CISA makes the application of the principle ne bis in idem subject to the condition of execution of the penalty. An analogous condition is not provided for in the Charter. These differences caused doubts regarding the application of the ne bis in idem principle and were subject of the question for preliminary ruling in the Spasic case (C-129/14 PPU). The paper contains a critical review of the reasoning of the Court of Justice of the European Union in this judgment. In addition, the article also contains an analysis of the CJEU’s decision in Case C-398/12 M. in which the CJEU has analysed the meaning of “final disposal” of the judgment in the context of the ne bis in idem principle. Based on the above judgments, the article presents arguments indicating that the reasoning of the CJEU on the conditions for the application of the ne bis in idem principle in judicial cooperation in criminal matters in the EU is not consistent.